Person deixis and impersonation in Iain Banks's Complicity. (February 2015) - Sorlin, Sandrine
The article focuses on the specific use of the second-person pronoun in Iain Banks's Complicity and the complex relationship it entertains with its first-person counterpart as the novel alternates between first- and second-person narratives. The personal pronouns construct two completely opposed mindstyles: the highly personal narrative of the first-person protagonist contrasts with the depersonalized style of the 'you' protagonist-narrator. Not only is the second-person pronoun a grammatical 'imposter' (Collins and Postal, 2012) – it actually hides an 'I' – but it is a psychological one as the narrator seems to hide his real self behind a convenient 'you persona'. In addition, the article brings to light the pragmatic paradox that 'self-address you' embodies in the peculiar position it assigns to the readers. If it tends to 'encroach upon' their territory, forcing them into complicity, it is also guilty of manipulating their emotions. Lastly, the linguistic and stylistic analysis of Banks's novel will here be coupled with cognitive and psycholinguistic approaches in order to understand how the reader switches from one 'frame' of mind to the other. Particularly helpful is the 'Rhetorical Processing Framework' discussed by Sanford and Emmott (2012) in order to grasp how readers construct mental representations to process the writer's sometimes misleading style.